The use of bacterial antibiotics extracted from Stenotrophomonas maltophilia to control plant fungal pathogens in vitro - Sazali, Nor Intan Syazwani (2016)
Fungal pathogens are known to cause important plant diseases which lead to significant lost in agricultural crops. The plant diseases need to be controlled to maintain the yield production and to avoid economic losses. Nowadays, people are aware of environmental issues caused by uncontrolled usage of synthetic fungicides. In response to this awareness, biological control using microbial antagonists is recommended instead of using synthetic chemicals for controlling plant diseases. Stenotrophomonas maltophilia can be used as a biological control agent against plant fungal pathogens. The bacterium can produce antibiotics that can inhibit pathogen growth and induce host resistance. In view of this, this research is conducted to 1) extract crude antibiotics from S. maltophilia and 2) study the effect of the crude antibiotics on the mycelial growth of selected plant fungal pathogens. This research used four different plant fungal pathogens which were Ganoderma boninense, Fusarium oxysporum, Rhizoctonia solani and Exserohilum rostratum. Crude antibiotics were extracted from bacterial culture in nutrient broth (NB) using centrifuge and lyophilization methods where the bacterial then was centrifuged to remove all bacterial cells and the supernatant was lyophilized in a vacuum evaporator. The four fungal pathogens were treated with five different concentrations of bacterial antibiotics which were 0.1, 0.2, 0.4, 0.8, 1.0 mg/L and control. The antagonism assay was done in five replications for each fungus and the experimental design was a Completely Randomized Design (CRD). Data were analysed using Analysis of Variance (ANOVA) from SAS version 9.4 and comparison of means with significant difference was further tested with Duncan‟s Multiple Range Test (DMRT). Each concentration significantly affected the percentage inhibition of diameter growth (PIDG) for all fungus (G. boninense, E. rostratum, R. solani and FOC). Extracted crude antibiotics from S. maltophilia was able to inhibit the mycelial growth of selected plant fungal pathogens at concentrations of 0.1, 0.2, 0.4, 0.8 and1.0 mg/L where concentration 1.0 mg/L gave the highest PIDG. R. solani showed the highest PIDG among all concentrations followed by G. boninense, E. rostratum and F. oxysporum.